2022
DOI: 10.1101/2022.05.26.493542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced memory precision in older age is associated with functional and structural differences in the angular gyrus

Abstract: Growing evidence indicates decreased fidelity of mnemonic representations to play a role in age-related episodic memory deficits, yet the brain mechanisms underlying such reductions remain unexplored. Using functional and structural neuroimaging and a continuous report task we examined how changes in two key nodes of the posterior-medial memory network, the hippocampus and the angular gyrus, might underpin loss of memory precision in older age. An age-related reduction in activity reflecting successful memory … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…While alternative strategy use has been favoured in previous studies as an explanation for unimpaired performance on tasks thought to require mental imagery by aphantasics (Jacobs et al, 2018;Keogh et al, 2021;Zeman et al, 2010), none until now have used probabilistic mixture modelling to investigate the visual fidelity of their memory representations, which should be particularly sensitive to the strength of visual imagery. Alternative probabilistic mixture models to the one used here can be applied to continuous report data (e.g., Bays, 2014), but two-component models describe this type of data well and have previously been used to separate long-term memory retrieval success and precision (Brady et al, 2013;Cooper et al, 2017Cooper et al, , 2019Harlow & Yonelinas, 2016;Korkki et al, 2020Korkki et al, , 2023Richter et al, 2016;Stevenson et al, 2018;Sutterer & Awh, 2016). Moreover, it should be noted that the current results did not change when a model-free measure of object memory performance, raw angular colour deviation, was analysed.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…While alternative strategy use has been favoured in previous studies as an explanation for unimpaired performance on tasks thought to require mental imagery by aphantasics (Jacobs et al, 2018;Keogh et al, 2021;Zeman et al, 2010), none until now have used probabilistic mixture modelling to investigate the visual fidelity of their memory representations, which should be particularly sensitive to the strength of visual imagery. Alternative probabilistic mixture models to the one used here can be applied to continuous report data (e.g., Bays, 2014), but two-component models describe this type of data well and have previously been used to separate long-term memory retrieval success and precision (Brady et al, 2013;Cooper et al, 2017Cooper et al, , 2019Harlow & Yonelinas, 2016;Korkki et al, 2020Korkki et al, , 2023Richter et al, 2016;Stevenson et al, 2018;Sutterer & Awh, 2016). Moreover, it should be noted that the current results did not change when a model-free measure of object memory performance, raw angular colour deviation, was analysed.…”
Section: Discussionmentioning
confidence: 80%
“…The CIELAB colour space is well suited for continuous manipulations of colour as a given distance between two colours in this space approximates their perceptual colour distance. This property of the CIELAB colour space has previously been leveraged to investigate the fidelity of both working memory retrieval (Bays et al, 2009;Zhang & Luck, 2008;Panichello et al, 2019) and long-term memory retrieval (Brady et al, 2013;Korkki et al, 2020Korkki et al, , 2023Richter et al, 2016). To minimise potential biases in colour memory, only objects without specific colour associations were selected for use as target stimuli in this study.…”
Section: Stimulimentioning
confidence: 99%
“…A high-fidelity representation closely matches the detail and complexity of the experience it is intended to capture. It has been suggested that the described age deficits arise in part from a decline in forming such high-fidelity, distinct representations and binding together stimulus features into qualitatively rich memory traces that allow for the veridical reinstatement of previously experienced events (Chen & Naveh-Benjamin, 2012; Fandakova et al, 2013, 2018; Koen & Rugg, 2019; Koen et al, 2020; Korkki et al, 2022; Naveh-Benjamin & Mayr, 2018; Park et al, 2012; Trelle et al, 2017).…”
Section: Summary Of the Aims And Hypotheses Of The Current Studymentioning
confidence: 99%